Nanoporous activated carbon from Bel fruit (Aegle marmelos) shell as efficient bio-adsorbent for river water treatment - Adhikari, Mandira Pradhananga; Regmi, Pushpa; Mishra, Sangita; Sapkota, Sabina; KC, Yojana; Sunwar, Bijaya; Yadav, Amar Prasad; Adhikari, Nanda Bikram (Scientific World, 2025)
Bel fruit (Aegle marmelos) shells were activated using phosphoric acid to synthesize nanoporous- activated carbons (ACs). The different ratios of bel shell powder to phosphoric acid were used to optimize the activating agent and then carbonized at 400 ℃ for three hours in a nitrogen atmosphere. The thermal stability of bel shell powder was determined using thermogravimetric analysis. Surface functional groups existing on the surface of bel shell-activated carbon were characterized using Boehm titration and Fourier Transform Infrared Spectroscopy (FTIR). The pore size was determined using iodine and methylene blue adsorption and surface morphology was analyzed using Scanning Electron Microscopy (SEM). The iodine adsorption was maximum (850.364 mg/g) at an impregnation ratio of 1:1.0 (precursor: phosphoric acid, BSC_1.0). The oxygenated functional groups such as hydroxyl, carbonyl and carboxyl present on the surface of the activated carbon (BSC_1.0) were confirmed by Boehm titration and FTIR analysis. Both Langmuir and Freundlich models fit well in methylene blue adsorption. The coefficient of the determinant was comparatively higher for the Langmuir model than the Freundlich model with an adsorption capacity of 227.27 mg/g. The remediation efficiency of bel shell-activated carbon was determined by treating Bagmati river water with BSC_1.0. The river water was black and found to be extremely polluted with -214 mV ORP, after treatment water turned into clean and clear and ORP enhanced to 91.0 mV. It removed more than 80% of contaminants from the river water, and significantly improved water quality to the WHO limits. Therefore, it is concluded that activated carbon from bel shells can be effectively used as bio-adsorbents for the remediation of Bagmati River water.